Associations of leptin and leptin receptor genetic variants with coronary artery disease: a meta-analysis. Issue 6 (10th June 2019) - Xiao, Peilin; Shi, Jianli; Liu, Xiaoli
Abstract : Background: Some pilot studies already tried to investigate potential associations of leptin ( LEP ) and LEP receptor ( LEPR ) variants with coronary artery disease (CAD). However, the results of these studies were not consistent. Thus, we performed the present meta-analysis to explore associations between LEP/LEPR variants and CAD in a larger pooled population. Methods: Systematic literature research of PubMed, Web of Science, Embase and CNKI was performed to identify eligible case–control studies on associations between LEP/LEPR variants and CAD. The initial search was conducted in September 2018 and the latest update was performed in December 2018. Q test and I 2 statistic were employed to assess between-study heterogeneities. If probability value( P -value) of Q test was less than 0.1 or I 2 was greater than 50%, random-effect models (REMs) would be used to pool the data. Otherwise, fixed-effect models (FEMs) would be applied for synthetic analyses. Results: A total of ten studies published between 2006 and 2018 were eligible for analyses (1989 cases and 2601 controls). Pooled analyses suggested that LEP rs7799039 variant was significantly associated with CAD under over-dominant model ( P =0.0007, odds ratio (OR) = 1.36, 95% confidence interval (CI): 1.14–1.63, I 2 = 41%, FEM) in overall population, and this significant finding was further confirmed in East Asians in subsequent subgroup analyses. However, no positive findings were observed for LEPR rs1137100 and rs1137101 variants in overall and subgroup analyses. Conclusions: Our meta-analysis suggested that LEP rs7799039 variant might affect individual susceptibility to CAD.